(untitled) (Fiep Bulletin - online, 2011)
This research was performed with a County Elementary School from Presidente Prudente in order to identify the conceptions of education and human development present in the speech of teachers and understand their significance, considering the importance of these categories and an adequate understanding of them, for the construction of an educational work differentiated in kindergarten. The participants were 10 teachers. It began with systematic observations at school and at monthly meetings of educational work. Later, there were semi-structured interviews with teachers to expand the data collection. With a theoretical-methodological support of cultural-history perspective, analyzing the data was found that teaching practices, as well as the teachers were saying about this practice have been marked by naive visions and naturalizing about children, often limiting the understanding of the development process of students to certain maturational biologizing; visions as well as limited when disconnected from objective reality of the subjects, the educational system and society as a whole, essential factors that need to be considered to think the process of human development at school . Contents related to the importance of care and affection in the relationship with students are evident, however, without valuing the teacher’s role as keeper of scientific knowledge in school. Often present simplistic and reductionist views that offer little benefit to a broader understanding about the child and their development processes. It was found that concepts presented about education and human development are supported by the empirical and daily experience of the teachers, instead of relating themselves about scientific knowledge of the issue. It appears that such views need to be overcome so that the conditions to implement a process of teaching and learning in science supported, especially in pedagogy and developmental psychology, to provide educational activities to enable the advancement of the subjects of early childhood education in a way fully and qualitatively high at school.